Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1111/j.1439-037x.2005.00161.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of N Fertilization Rate on Sugar Yield and Non‐Sugar Impurities of Sugar Beets (Beta vulgaris) Grown Under Mediterranean Conditions

Abstract: For three successive growing seasons (1999–2001), a completely randomized block design experiment was established at the surrounding area of each of four sugar beet processing plants of Hellenic Sugar Industry SA, Greece (a total of 12 experiments). Nitrogen was applied at five rates (0, 60, 120, 180 and 240 kg N ha−1) and six replications per rate. Nitrogen fertilization had site‐specific effects on quantitative (fresh root and sugar yields) and qualitative (sucrose content, K, Na, α‐amino N) traits. When dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 17 publications
3
32
0
2
Order By: Relevance
“…Sodium and a-amino N increase significantly at site B whereas sugar content and purity decreased. Min-N increased potassium concentration in the beets less than sodium and a-amino N. This confirms previous observations by Tsialtas and Maslaris (2005) and Stevanato et al (2010b). The difference in sugar yield between sites is not significant, but, owing to the different processing quality, the extractable sugar yield becomes significant.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Sodium and a-amino N increase significantly at site B whereas sugar content and purity decreased. Min-N increased potassium concentration in the beets less than sodium and a-amino N. This confirms previous observations by Tsialtas and Maslaris (2005) and Stevanato et al (2010b). The difference in sugar yield between sites is not significant, but, owing to the different processing quality, the extractable sugar yield becomes significant.…”
Section: Resultssupporting
confidence: 90%
“…Samples were collected in February, at the beginning of soil warming and the period of more intense organic matter mineralization. The amount of min-N available for plants could therefore increase according to the rising soil temperature (Bilbao et al 2004;Tsialtas and Maslaris 2005).…”
Section: Soil Analysesmentioning
confidence: 99%
“…The N level of 350 kg/ha gave the highest impurities, but purity % found to increase by the application of this N rate. Some reports indicated that excess N fertilizer may decrease sugar %, lowering the recoverable sugar and increasing the impurities such as proteins, α-amino N and Na contents (Tsialtas and Maslaris 2005, Manderscheid et al 2010, Mekdad 2015. Micronutrients are important to plant growth and productivity that are the macronutrients in the soils.…”
Section: Discussionmentioning
confidence: 99%
“…Utilization of nitrogen enhanced sugar percentage, root and sugar yield for sugar beet plants (Tsialtas andMaslaris, 2005 andMekdad andRady, 2016). Increasing nitrogen enhance significantly yield and quality of sugar beet plants Mekdad (2015).…”
Section: Introductionmentioning
confidence: 99%